eCM 2017
DOI: 10.22203/ecm.v033a12
|View full text |Cite
|
Sign up to set email alerts
|

Lengthening primary cilia enhances cellular mechanosensitivity

Abstract: The primary cilium is a mechanosensor in a variety of mammalian cell types, initiating and directing intracellular signaling cascades in response to external stimuli. When primary cilia formation is disrupted, cells have diminished mechanosensitivity and an abrogated response to mechanical stimulation. Due to this important role, we hypothesized that increasing primary cilia length would enhance the downstream response, and therefore, mechanosensitivity. To test this hypothesis, we increased osteocyte primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 65 publications
1
84
1
Order By: Relevance
“…Furthermore, in mesenchymal stem cells, primary cilia are necessary for mechanosignalling [47] which also regulated differentiation. Other recent studies report that cilia elongation increases mechanosignalling in bone [48]. Therefore changes in cilia length in response to osteogenic TCP topography may modulate in vivo bone formation through altered mechanosignalling in addition to regulation of osteogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, in mesenchymal stem cells, primary cilia are necessary for mechanosignalling [47] which also regulated differentiation. Other recent studies report that cilia elongation increases mechanosignalling in bone [48]. Therefore changes in cilia length in response to osteogenic TCP topography may modulate in vivo bone formation through altered mechanosignalling in addition to regulation of osteogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…FGF was believed to act independently of the cilium until a study revealed that cilia shorten in zebrafish embryos containing a knockdown of FGF receptor 1 (FGFR1) . Recent work in our lab and others suggests that lengthening cilia enhances their mechanosensitivity, so it is perhaps not surprising that FGF mutants with shorter cilia demonstrate developmental abnormalities . In the growth plate, FGF signaling inhibits chondrocyte proliferation and accelerates the onset and rate of hypertrophic differentiation .…”
Section: Ciliary Signaling Pathways Regulate Growth Plate Developmentmentioning
confidence: 99%
“…We recently showed that treating osteocytes with fenoldopam or lithium, two small molecules with distinct mechanisms of action, increases primary cilia length [77]. Moreover, osteocytes with longer cilia are more mechanosensitive, displaying increased osteogenesis in response to fluid flow.…”
Section: Primary Cilia Structure Dictates Mechanosensingmentioning
confidence: 99%
“…Longer cilia may allow for a greater number of cilia-specific proteins and signaling molecules within the microdomain to potentiate mechanosensing [52,54]. Cells treated with the cilium lengthening agent, fenoldopam, also display significant increases in production of AC6, key to primary cilia-mediated mechanotransduction [77,78]. …”
Section: Primary Cilia Structure Dictates Mechanosensingmentioning
confidence: 99%